Single-dose live-attenuated vesicular stomatitis virus-based vaccine protects African green monkeys from Nipah virus disease. Issue 24 (4th June 2015) - Prescott, Joseph; DeBuysscher, Blair L.; Feldmann, Friederike; Gardner, Donald J.; Haddock, Elaine; Martellaro, Cynthia; Scott, Dana; Feldmann, Heinz
Highlights: Nipah virus causes severe human disease and there is no approved vaccine or therapeutic. Attenuated VSV vaccines that express Nipah proteins are efficacious in African green monkeys. A single administration prevents virus shedding, replication and Nipah virus disease. The rapid time to immunity is advantageous in outbreak situations for 'ring vaccination'. Abstract: Nipah virus is a zoonotic paramyxovirus that causes severe respiratory and/or encephalitic disease in humans, often resulting in death. It is transmitted from pteropus fruit bats, which serve as the natural reservoir of the virus, and outbreaks occur on an almost annual basis in Bangladesh or India. Outbreaks are small and sporadic, and several cases of human-to-human transmission have been documented as an important feature of the epidemiology of Nipah virus disease. There are no approved countermeasures to combat infection and medical intervention is supportive. We recently generated a recombinant replication-competent vesicular stomatitis virus-based vaccine that encodes a Nipah virus glycoprotein as an antigen and is highly efficacious in the hamster model of Nipah virus disease. Herein, we show that this vaccine protects African green monkeys, a well-characterized model of Nipah virus disease, from disease one month after a single intramuscular administration of the vaccine. Vaccination resulted in a rapid and strong virus-specific immune response which inhibited virus shedding and replication. This vaccine platform provides a rapid means to afford protection from Nipah virus in an outbreak situation.